Constituents of Low Value Trawl By-catch Caught off Veraval - putra, Pravin; R.C., Manohardoss (Fishery Technology, 2025)
87 species belonging to 42 families were recorded in the low value by-catch from small and medium mechanised trawlers based at Veraval, Gujarat. Percentage contribution of these species in the by-catch has been worked out.